Immunogenetic Study in Chinese Population with Ankylosing Spondylitis: Are There Specific Genes Recently Disclosed? - Jiayu Zhai; Ju Rong; Qiuxia Li; Jieruo Gu (Clinical and Developmental Immunology)
Purpose. Ankylosing spondylitis (AS) is a systemic, autoimmune disease resulting in the destruction of the affected joints. Over the past 5 years, several new genes or genetic regions associated with AS have been identified in the Chinese population. This paper aims to discuss the major findings and related potential mechanisms of these studies in our population. Recent Findings. In recent years, due to the rapid advances in computational genetics and technology, there has been an increasing list of well-validated genes or genetic regions associated with AS susceptibility. So far, several genes or genetic regions have now been reported in the Han ethnic Chinese population, containing the major histocompatibility complex (MHC), ERAP1, IL-23R, 12q12, 2p15, 5q14.3, and so on. Different hypotheses for disease mechanisms have been investigated on the basis of the functional studies of these genes or genetic regions. Summary. This paper tries to summarize the association of several candidate genes with risk for AS in the Han ethnic Chinese population and aims to identify the novel inflammatory pathways and provide potential strategies for better therapies.